Performance of Asphalt Wearing Course Against The Immersion Effect Of Tide Water (Rob) With Added Materials Polyethylene And Fine Aggregate Slag - Juny Andry Sulistyo; P Pratikso; Rachmat Mudiyono (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
Rob or tide water is a flood of seawater or rising sea level caused by high tide inundating land. Heavy traffic and tidal immersion on main roads result in permanent deformation require quality asphalt that is resistant to tidal immersion and traffic loads. The use of a combination of LDPE and aggregate slag is an unprecedented update. Polyethylene (PE) plastic waste provides water resistance therefore the combination can be a new Job Mix Formula that is able to withstand tidal immersion (rob) allowing it to be used in the construction of road structures (Flexible Pavement). The duration of immersion is 7 days, 14 days and 21 days and the soaking method consists of immerse with a continuous pattern and soaking with a periodic / cyclic pattern (intermittent). Job Mix Formula that can be used on asphalt concrete wearing course modification is a combination of 50% Slag aggregate and 6% LDPE while asphalt concrete wearing course modification of 0% and 100% Slag Aggregate grades with LDPE 0%, 2%, 4%, 8%, 10% and 18% cannot be used as road pavement because it does not meet the requirements of Bina Marga technical specifications.